2023
DOI: 10.1101/2023.02.23.529715
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HilE represses the activity of HilD via a mechanism distinct from that of intestinal long-chain fatty acids

Abstract: The expression of virulence factors essential for the invasion of host cells by Salmonella enterica is tightly controlled by a network of transcription regulators. The AraC/XylS transcription factor HilD is the main integration point of environmental signals into this regulatory network, with many factors affecting HilD activity. Long chain fatty acids (LCFAs), which are highly abundant throughout the host intestine directly bind to, and repress HilD, acting as environmental cues to coordinate virulence gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 69 publications
2
13
0
Order By: Relevance
“…No activity of CDCA was observed at the highest tested concentration of 100 µM. These data are in line with the reported activities of the FAs 39 and CDCA 35 , and therefore confirm the reliability of the assay to quantify HilD transcriptional activity.…”
Section: Mainsupporting
confidence: 89%
See 4 more Smart Citations
“…No activity of CDCA was observed at the highest tested concentration of 100 µM. These data are in line with the reported activities of the FAs 39 and CDCA 35 , and therefore confirm the reliability of the assay to quantify HilD transcriptional activity.…”
Section: Mainsupporting
confidence: 89%
“…The bile acid CDCA has been shown to interfere with HilD dimerization and DNA binding 35 . Similarly, long chain fatty acids (LCFAs) have been shown to bind to HilD and block its dimerization 32,39 . We showed that C26 shares the same binding pocket as CDCA and LCFAs, however, its binding mode is suggested to be different since the inhibition occurs without interfering with the dimerization of the protein.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations